Facing emotions: real-time fMRI-based neurofeedback using dynamic emotional faces to modulate amygdala activity - Watve, Apurva; Haugg, Amelie; Frei, Nada; Koush, Yury; Willinger, David; Bruehl, Annette Beatrix; Stämpfli, Philipp; Scharnowski, Frank; Sladky, Ronald (Frontiers in Neuroscience, 2024)
Maladaptive functioning of the amygdala has been associated with impaired emotion regulation in affective disorders. Recent advances in real-time fMRI neurofeedback have successfully demonstrated the modulation of amygdala activity in healthy and psychiatric populations. In contrast to an abstract feedback representation applied in standard neurofeedback designs, we proposed a novel neurofeedback paradigm using naturalistic stimuli like human emotional faces as the feedback display. The feasibility of this experimental approach was tested on sixty-four healthy participants who completed a single training session with four neurofeedback runs. Participants were assigned to one of the four experimental groups (n=16 per group), i.e., happy-up, happy-down, fear-up, fear-down. Depending on the group assignment, they were either instructed to ‘try to make the face happier’ by upregulating (happy-up) or downregulating (happy-down) the amygdala or to ‘try to make the face less fearful’ by upregulating (fear-up) or downregulating (fear-down) the amygdala feedback signal. The change in the facial expression intensity (from neutral to happy or from fearful to neutral) was coupled with the participant’s ongoing bilateral amygdala activity. Linear mixed effect analyses revealed significant amygdala activity changes in the fear condition, specifically in the fear-down group with significant amygdala downregulation in the last two neurofeedback runs as compared to the first run. The happy-up and happy-down groups did not show significant amygdala activity changes over four runs. We did not observe significant improvement in the questionnaire scores and subsequent behavior. Furthermore, task-dependent effective connectivity changes between the amygdala, fusiform face area (FFA), and the medial orbitofrontal cortex (mOFC) were examined using dynamic causal modelling. The effective connectivity between FFA and the amygdala was significantly increased in the happy-up group (facilitatory effect) and decreased in the fear-down group. Notably, the amygdala was downregulated through an inhibitory mechanism mediated by mOFC during the first training run. Here, we intended to address key neurofeedback processes like naturalistic facial stimuli, participant engagement in the task, bidirectional regulation, task congruence, and their influence on learning success. This feasibility study demonstrated that. Such a versatile emotional face feedback paradigm can be tailored to target biased emotion processing in affective disorders.